Encouraging Motivation: Teaching Strategies for Multilingual Learners (European Journal of Teaching and Education, 2025)
Multilingual learners are an ever growing segment of the student population. This article recognizes the need for teaching strategies that address this reality. Lesson plans containing motivational elements will help multilingual learners achieve academic success. This study touches on three motivational factors – self efficacy, relevance, and collaboration. It examines ways these factors are incorporated into lesson planning and measures effectiveness through data collection in Action Research. The framework incorporates Stephen Krashen’s theory of lowering the affective filter (1985) and Maslow’s hierarchy of needs (1943) to tap into students’ prior knowledge and promote academic achievement.